Hard-boiled wonderland and the end of the world. - Murakami, Haruki, ....- (London : Vintage Books, 2003)
The last surviving victim of an experiment that implanted the subjects' heads with electrodes that decipher coded messages is the unnamed narrator of this excellent book by Murakami, one of Japan's best-selling novelists and winner of the prestigious Tanizaki prize. Half the chapters are set in Tokyo, where the narrator negotiates underground worlds populated by INKlings, dodges opponents of both sides of a raging high-tech infowar, and engages in an affair with a beautiful librarian with a gargantuan appetite. In alternating chapters he tries to reunite with his mind and his shadow, from which he has been severed by the grim, dark "replacement" consciousness implanted in him by a dotty neurophysiologist. Both worlds share the unearthly theme of unicorn skulls that moan and glow. Murakami's fast-paced style, full of hip internationalism, slangy allegory, and intrigue, has been adroitly translated. Murakami is also author of A Wild Sheep Chase ( LJ 10/15/89); his new work is recommended for academic libraries and public libraries emphasizing serious contemporary fiction.
Keywords: Roman